Age- and Diet-Dependent Changes in Hepatic Lipidomic Profiles of Phospholipids in Male Mice: Age Acceleration in Cyp2b-Null Mice. (29th March 2022) - Heintz, Melissa M.; Kumar, Ramiya; Maner-Smith, Kristal M.; Ortlund, Eric A.; Baldwin, William S.
Abstract : Increases in traditional serum lipid profiles are associated with obesity, cancer, and cardiovascular disease. Recent lipidomic analysis has indicated changes in serum lipidome profiles, especially in regard to specific phosphatidylcholines, associated with obesity. However, little work has evaluated murine hepatic liver lipidomic profiles nor compared these profiles across age, high-fat diet, or specific genotypes, in this case the lack of hepatic Cyp2b enzymes. In this study, the effects of age (9 months old), high-fat diet (4.5 months old), and the loss of three primarily hepatic xeno- and endobiotic metabolizing cytochrome P450 (Cyp) enzymes, Cyp2b9, Cyp2b10, and Cyp2b13 (Cyp2b-null mice), on the male murine hepatic lipidome were compared. Hierarchical clustering and principal component analysis show that age perturbs hepatic phospholipid profiles and serum lipid markers the most compared to young mice, followed by a high-fat diet and then loss of Cyp2b. Several lipid biomarkers such as PC/PE ratios, PE 38 : 6, and LPC concentrations indicate greater potential for NAFLD and hypertension with mixed effects in Cyp2b-null mice(less NAFLD and greater hypertension-associated markers). Lipid profiles from older mice contain greater total and n-6 fatty acids than normal diet (ND)-fed young mice; however, surprisingly, young Cyp2b-null mice contain high n-6 : n-3 ratios. Overall, the lack of Cyp2b typically enhanced adverse physiological parameters observed in the older (9 mo) mice with increased weight gain combined with a deteriorating cholesterol profile, but not necessarily all phospholipid profiles were adversely perturbed.